Gestión microcurricular para optimizar la enseñanza de los docentes frente a la reforma de sexto y séptimo grado de Educación General Básica ( E.G.B.) en las escuelas " Alberto Soberón", "Carlos Larco", "Leopoldo Mercado", en la provincia de Pichincha. Programa de capacitación de los componentes microcurriculares. - Montero Olmedo, Rubí Martha (2015)
Nowadays many institutions from different sectors of our country are concerned about the different changes that have undergone the Consensus Curriculum Reform for the Ecuadorian basic education. Which was presented to the country in 1996 and then in 2010 .The present research has its aims focused to implement a training program for teachers of sixth and seventh grade of Alberto Soberón, Carlos Hidalgo and Leopoldo Mercado schools, in the province of Pichincha, in order to optimize the teaching processes. The program provides useful information to any institution or individual teacher, because it helps to improve the development of micro curricular planning’s, face to the demands of the modern society, the requirements, the demanded of the Organic Law of Intercultural Education, Updating and Strengthening Curriculum, it forces the teacher to fulfill cognitive, procedural and attitudinal actions, where the direct beneficiaries are the students, who receive quality care and warmth services, it can be applied in a specific institution the practice of micro curricular management, which will take place in our professional life. This training program will serve as a guide in the management of micro curricular components, so at all times that planning must be effective in its three components: the teacher, students and content, benefiting in a good manner to the teachers for planning their academic activities, and in this way they manage and optimize the teaching processes, so it is recommended to maintain a continuity of the training program to get the objectives which are aligned to knowledge, actions, attitudes, procedures and achievement of learning set out in the curriculum, which skills and abilities are running on by the teacher during the teaching learning process in a real and efficient way in each of the institutions.